Hemostasis-on-a-chip / incorporating the endothelium in microfluidic models of bleeding. (31st December 2023) - Sakurai, Yumiko; Hardy, Elaissa T.; Lam, Wilbur A.
Abstract: Currently, point-of-care assays for human platelet function and coagulation are used to assess bleeding risks and drug testing, but they lack intact endothelium, a critical component of the human vascular system. Within these assays, the assessment of bleeding risk is typically indicated by the lack of or reduced platelet function and coagulation without true evaluation of hemostasis. Hemostasis is defined as the cessation of bleeding. Additionally, animal models of hemostasis also, by definition, lack human endothelium, which may limit their clinical relevance. This review discusses the current state-of-the-art of hemostasis-on-a-chip, specifically, human cell-based microfluidic models that incorporate endothelial cells, which function as physiologically relevant in vitro models of bleeding. These assays recapitulate the entire process of vascular injury, bleeding, and hemostasis, and provide real-time, direct observation, thereby serving as research-enabling tools that enhance our understanding of hemostasis and also as novel drug discovery platforms. Plain Language Summary: The human body's response to stop bleeding after a vascular injury involves a complex but finely tuned cascade of interactions between the blood, the blood vessel wall, and the physical flow of the blood. Accordingly, in vitro models that incorporate those aspects that occur in vivo are highly needed for research and clinical purposes. Here, we review the state of the art of these technologies, hemostasis-on-a-chip devices that aim to achieve those goals. These physiologically relevant "microchips" mimic the bleeding process as well as the cessation thereof, and can be leveraged as research-enabling tools, platforms for drug discovery, and clinical testing.